Synthesis and Crystal Structure of Mn(II) Complex with 2,9-Bis(n-2’,5’-diazaheptanyl)-1,10-phenanthroline - LI, FENG-HUA; LIU, TIAN-FU; LIN, HUA-KUAN; LI, XUE-MEI; ZHANG, SHU-SHENG (Asian Journal of Chemistry, 2010)
<!– [if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!– [if gte mso 9]> <![endif]–><!– [if gte mso 10]> <![endif]–> A new complex [MnL][MnCl4]·0.5C2H5OH, of which L represents 2,9-bis(n-2',5'-diazaheptanyl)-1,10-phenanthroline, has been synthesized and structurally determined by X-ray diffraction analysis. It crystallizes in the monoclinic system, space group P2(1)/c, with a = 13.676(4) Å, b = 11.255(4) Å, c = 20.153(7) Å, β = 105.101(5)°, Mr = 655.25, V = 2995.0(17) Å3, Z = 4, Dc = 1.453 Mg/m3, μ = 1.225 mm-1 and final R = 0.0466. The complex consists of one [MnL]2+ cations, one [MnCl4]2- anion and half alcohol molecule. The Mn(II) ion is coordinated by six nitrogen atoms of the ligand, in which the two nitrogen from the phenanthroline and the two from the imine groups near the phenanthroline are in the equatorial plane while the two from the imine groups at the end of both arms in the axial positions. Hydrogen bonds are formed between the chlorine ions of MnCl42- and the adjacent hydrogen atoms of imine group.